Nonconscious Lyric: Ferdinand de Saussure and Poetry's Computational Origin. - Slater, Avery (Modern Philology, 2024)
This essay revisits Ferdinand de Saussure's conjecture that lyric poetry originates from a technique of phonemic patterning that he termed "hypograms." Examining lyric practice through the hypogram, Saussure proceeded from saturnian verse to a study of Homer, Virgil, and Lucretius, discovering a complex, combinatorial process of syllabic recombination and dispersal. His theories, never published in his lifetime, resurfaced in the poststructuralist moment and were used to reframe Saussure's contribution as a defiance of those systems and linguistic laws for which he was known. Yet in removing Saussure's hypograms from the overall program of structuralism, a fundamental insight of the theory was elided: the coded and computational origin of the lyric in the human mind. This essay considers the hypogram as an artifact of nonconscious cognition, whose patterned and combinatorial generativity underlies poetic composition. Unlike consciously perceptible and prominent forms of linguistic patterning such as rhyme, the hypogram's origination and registration proceeds nonconsciously. Decrypting the lyric hypogram provides a glimpse into the cognitive "mechanisms" of linguistic computation that enable the generation of poetry and language use more generally.